Therapeutic Effect of Shikimic Acid on Heat Stress-Induced Myocardial Damage: Assessment via Network Pharmacology, Molecular Docking, Molecular Dynamics Simulation, and In Vitro Experiments - Yan Gu; Jingyi Zhang; Haohong Zheng; Yuyang Qin; Min Zheng; Yanchun Hu; Jialiang Xin (Pharmaceuticals)
Abstract: Background: Rising global temperatures have been linked to an increased incidence of heat stress (HS)-induced myocardial damage. Methods: This study aimed to investigate the therapeutic potential of shikimic acid (SA) on HS-induced myocardial damage using network pharmacology, molecular docking, molecular dynamics (MD) simulations, and in vitro experiments. Results: Network pharmacology analysis indicated that SA significantly attenuates the inflammatory response to HS by modulating 60 targets, including TNF, IL-6, and STAT3, which are enriched in the PI3K/AKT signaling pathway. Molecular docking and MD simulation analyses demonstrated that SA forms stable complexes with TNF (−6.642 kcal/mol) and IL-6 (−7.261 kcal/mol), with no significant conformational changes over a 100 ns simulation period. In vitro experiments demonstrated that SA, within the concentration range of 250 μM to 31.25 μM, significantly promoted the proliferation of normal HL-1 cells by an average of 31.0%. Moreover, it enhanced the survival rate of HL-1 cells exposed to 43 °C for 3 h by approximately 59.9% and downregulated the expression of Hsp90 and Hsp70. Additionally, this concentration range of SA reduced the expression of TNF-α, IL-6, TLR2, and COL1A1. Conclusions: These findings offer evidence for the therapeutic potential of SA in HS-induced myocardial damage.